pH-thermoreversible hydrogels. I. Synthesis and characterization of poly(N-isopropylacrylamide/maleic acid) copolymeric hydrogels - KAYAMAN APOHAN, NİLHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
N-isopropylacrylamide (NIPAAM)/maleic acid (MA) copolymeric hydrogels were prepared by irradiating the ternary mixtures of NIPAAM/MA/Water by gamma-rays at ambient temperature. The influence of external stimuli such as pH and temperature of the swelling media on the equilibrium swelling properties was investigated. The hydrogels showed both temperature and pH responses. The effect of comonomer concentration and irradiation dose on the swelling equilibria and phase transition was studied. For the characterization of these hydrogels, the diffusion behaviour and molecular weight between crosslinks were investigated. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: hydrogel; copolymers; N-isopropylacrylamide; LCST; maleic acid; gamma-rays; SWELLING BEHAVIORS; CONTROLLED-RELEASE; TEMPERATURE; ADSORPTION; COMONOMER; WATER; GELS